The new informatics of pandemic response: humanitarian technology, efficiency, and the subtle retreat of national agency - Wilson, Christopher (Journal of International Humanitarian Action, 2018)
Digital communication technologies play an increasingly prominent role in humanitarian operations and in response to international pandemics specifically. A burgeoning body of scholarship on the topic displays high expectations for such tools to increase the efficiency of pandemic response. This article reviews empirical uses of communications technology in humanitarian and pandemic response, and the 2014 Ebola response in particular, in order to propose a three-part conceptual model for the new informatics of pandemic response. This model distinguishes between the use of digital communication tools for diagnostic, risk communication, and coordination activities and highlights how the influx of novel actors and tendencies towards digital and operational convergence risks focusing humanitarian action and decision-making outside national authorities’ spheres of influence in pandemic response. This risk exacerbates a fundamental tension between the humanitarian promise of new technologies and the fundamental norm that international humanitarian response should complement and give primacy to the role of national authorities when possible. The article closes with recommendations for ensuring the inclusion of roles and agency for national authorities in technology-supported communication processes for pandemic response.